Energy harvesting based on compressive stress-induced ferroelectric/ferroelastic switching in polycrystalline ferroelectric materials - Kang, W; Huber, J (Elsevier, 2021)
Although piezoelectric energy harvesting is well established, ferroelectric/ferroelastic switching has not been widely used for energy harvesting. The main disadvantage of piezoelectric energy harvesters is their limited power density. In this respect, ferroelectric/ferroelastic switching is attractive because of the greater energies and charge flows involved. However, the associated nonlinearities and the difficulty of establishing a stable working cycle have prevented significant progress. In this work, a robust ferroelectric energy harvester based on partial ferroelectric switching is explored. The device is of simple construction and achieves a per-cycle energy density of about 1 mJ cm−3, orders of magnitude greater than that of typical piezoelectrics. It is shown that only periodic compressive stress is needed to induce the energy harvesting cycles, yielding promising mechanical attributes that limit fatigue or fracture during cyclic loading. The results show this prototype device operating stably over 0.5 × 106 cycles at 20-Hz frequency, demonstrating promise for practical applications.